Indigenous diazotrophs and their effective properties for organic agriculture - Thi Hieu Thu, Nguyen; Cao Son, Trinh; Thu Trang, Dang; Thi My Le, Nguyen; Duy Toi, Nguyen; Thi Van, Nguyen; Thuy Hang, Dinh (Vietnam Journal of Biotechnology, 2022)
Nitrogen-fixing microorganisms (diazotrophs) converting the atmospheric N2 into usable form NH4 are considered the key players in the nitrogen cycle, chiefly responsible for the enriching nitrogen content in the soils. Globally, biological fixation of N2 greatly contributes to plant growth, lessens the need for chemical fertilizers, and thus contributes to the mitigation of greenhouse gases NOx. In this study, diazotrophic bacterial strains were isolated from rhizosphere soils and root nodules of legume and non-legume plants in Vietnam. Quantitative analyzes by the acetylene reduction assay showed that the isolates have high nitrogen fixation activity compared with that of reference strain Azospirillum vinelandii KCTC 2426. In addition, other effective capabilities of the isolated strains toward supporting agriculture were investigated, i.e. synthesizing IAA and siderophore for promoting plant growth, or producing exopolysaccharides for maintaining soil moisture. Taxonomic positions of the isolated strains were identified based on the comparative analyses of sequences of the 16S rDNA and gene related to nitrogen fixation (nifH), revealing a high taxonomic diversity among free-living and symbiotic diazotrophic isolates. Direct support of the selected isolates to plant growth was proven in experiments with mung beans under laboratory conditions. Thus, the native diazotrophic strains obtained in this study would be good microbial sources for application in organic agriculture and soil amendment.